2000
DOI: 10.1093/emboj/19.16.4204
|View full text |Cite
|
Sign up to set email alerts
|

The structure of L-amino acid oxidase reveals the substrate trajectory into an enantiomerically conserved active site

Abstract: The structure of L-amino acid oxidase (LAAO) from Calloselasma rhodostoma has been determined to 2.0 A Ê resolution in the presence of two ligands: citrate and o-aminobenzoate (AB). The protomer consists of three domains: an FAD-binding domain, a substrate-binding domain and a helical domain. The interface between the substrate-binding and helical domains forms a 25 A Ê long funnel, which provides access to the active site. Three AB molecules are visible within the funnel of the LAAO±AB complex; their orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
232
2
13

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(258 citation statements)
references
References 41 publications
11
232
2
13
Order By: Relevance
“…The FAD-binding patterns of GO, DAAO, and MSOX share an overall similarity; in all these enzymes the FAD-binding domain contains the conserved Rossmann fold ␤␣␤ motif (␤1, ␣1, and ␤2) (33), which serves as a dinucleotide-binding motif (35). The central part of this consensus motif is the sequence GXGXXG (Gly 11 , Gly 13 , and Gly 16 of helix ␣1) with the N-terminal end of helix ␣1 pointing toward the FAD pyrophosphate moiety, as observed for other dinucleotide-binding proteins (35). The binding of FAD in GO is that typical of the GR 2 subfamily (34); the prosthetic group adopts an extended conformation with the isoalloxazine ring located at the interface between the FAD-binding domain and the substrate-binding domain, facing with its re-side the inner part of the substrate-binding cavity.…”
Section: Resultsmentioning
confidence: 99%
“…The FAD-binding patterns of GO, DAAO, and MSOX share an overall similarity; in all these enzymes the FAD-binding domain contains the conserved Rossmann fold ␤␣␤ motif (␤1, ␣1, and ␤2) (33), which serves as a dinucleotide-binding motif (35). The central part of this consensus motif is the sequence GXGXXG (Gly 11 , Gly 13 , and Gly 16 of helix ␣1) with the N-terminal end of helix ␣1 pointing toward the FAD pyrophosphate moiety, as observed for other dinucleotide-binding proteins (35). The binding of FAD in GO is that typical of the GR 2 subfamily (34); the prosthetic group adopts an extended conformation with the isoalloxazine ring located at the interface between the FAD-binding domain and the substrate-binding domain, facing with its re-side the inner part of the substrate-binding cavity.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the low sequence similarity, the topology of MAO, modeled from PAO, also closely resembles that of L-amino acid oxidase (42) with further similarities to D-amino acid oxidase (43) and p-hydroxybenzoate hydroxylase (44). Within this family of flavoproteins, most structural differences appear in the helical (interface) domain (42).…”
Section: Modeling Of Mao a And Mao B-mentioning
confidence: 99%
“…Within this family of flavoproteins, most structural differences appear in the helical (interface) domain (42).…”
Section: Modeling Of Mao a And Mao B-mentioning
confidence: 99%
“…It constitutes 1-9% of the total venom protein and is responsible for the light yellowish color of the venom and catalyzes the stereospecific de-amination of an L-amino acid substrate to an alpha-keto acid along with the production of ammonia and hydrogen peroxide. It has been found that LAAO from snake venom can induce apoptosis in mammalian endothelial cells possible due to the production of high concentration of hydrogen peroxide (Pawelek et al, 2000).…”
Section: L-amino Acid Oxidase (Laao)mentioning
confidence: 99%
“…LAAOs are dimeric flavoprotein that contains a non-covalently bound FAD as a co-factor (Pawelek et al, 2000). LAAOs isolated from Ophiophagus hannah venom decreases thymidine uptake in murine melanoma, fibrosarcoma, colorectal cancer and Chinese hamster ovary cell line that also showed reduction in cellular proliferation (Cura et al, 2002).…”
Section: Anticancer Activity Of Snake Venommentioning
confidence: 99%